Social representations of health warnings among smokers and nonsmokers university students - Siqueira, Cibele Leite; Leite, Tânia Maria Coelho (Rev Rene, 2012)
Smoking is considered by the World Health Organization as an epidemic disease and serious public health problem. Thus, health warnings printed on cigarette packs have been imposed by lawmakers. The objective was to show the college smokers and nonsmokers the health warnings on cigarette packs. A qualitative research was used based on social representation. 25 subjects were interviewed, of whom 11 were smokers. The categories emerged from the analyses: the meaning of illness, negative feeling, aversion to the images, the meaning of death, the third person effect, and negative feelings related to smoking and family awareness. We found that tobacco users recognize the dangers of its use, have negative feelings about the pictures, but they show aversion to this kind of warning. We emphasize the need for educational measures by nurses, educating the public regarding the use of tobacco.